A Flexible Approach to Semantic Annotation Systems for Web Content. Issue 1 (27th January 2015) - Fiorelli, Manuel; Pazienza, Maria Teresa; Stellato, Armando
Summary In this paper we propose a flexible approach that supports heterogeneous requirements on systems for the semantic annotation of web content. The flexibility of the approach originates from a model based on the definition of abstract events, which captures at the logical level the main interactions occurring in a system for combined management of ontologies and web content. Application‐specific semantics is then provided operationally as an assignment of handlers to these events. While the abstract events are rather coarse‐grained to reduce prior commitment, preconditions on the handlers express application‐specific distinctions based on contextual information associated with each specific event. Although the possibility to define completely new handlers guarantees the generality of our approach, we foster convention over configuration by providing a set of default handlers, which can be customized by filling their extension points. The use of customizable handlers, whether or not the default ones, reduces the development effort and guarantees consistent user experience despite evolving requirements. A comprehensive framework for semantic annotation of web content has been realized and will be hereafter introduced. Copyright © 2015 John Wiley & Sons, Ltd.